"I`d got self-destruction down to a fine art": a qualitative exploration of relative energy deficiency in sport (RED-S) in endurance athletes - Langbein, R. K.; Martin, D.; Allen-Collinson, J.; Crust, L.; Jackman, P. C. (Journal of Sports Sciences, 2021)
Relative Energy Deficiency in Sport (RED-S) is a syndrome of impaired health and performance that occurs as a result of low energy availability (LEA). Whilst many health effects associated with RED-S have been widely studied from a physiological perspective, further research exploring the psychological antecedents and consequences of the syndrome is required. Therefore, the aim of this study was to qualitatively explore athlete experiences of RED-S. Twelve endurance athletes (female n= 10, male n= 2; M age = 28.33 years) reporting past or current experiences of RED-S, associated with periods of LEA, took part in semi-structured interviews designed to explore: contexts and mechanisms underpinning the onset of RED-S; the subjective experience of RED-S; and contexts and mechanisms influencing "recovery" from RED-S. Regardless of how RED-S was initiated, all athletes experienced a multitude of physiological impairments, accompanied by significant psychological distress. This paper contributes novel understanding of the complex interplay between physiological and psychological components of RED-S from the perspective of information-rich cases. The findings suggest that system-wide educational prevention and awareness interventions are vital for athletes and support personnel, such as coaches, parents, dieticians, psychologists, and sports medicine staff.